PEMENUHAN KEBUTUHAN VITAMIN DAN MINERAL PADA PASIEN GAGAL GINJAL KRONIK DI RSUD DR. SOEKARDJO TASIKMALAYA - Hartati Pratiwi, Sri; Nurkarimah, Asri; Rahayu, Urip (LPPM STIKES MUHAMMADIYAH GOMBONG, 2018)
Renal failure patients will experience a variety of metabolic disorders included in the production process of various vitamins and minerals. Lack of vitamin and mineral intake will aggravate vitamin and mineral deficiencies so that patients can experience various musculoskeletal disorders. This condition can cause deterioration in the patient's condition so that the quality of life of the patient can decrease. This study aims to identify the fulfillment of vitamin and mineral needs in patients with chronic kidney diseases.This research used descriptive quantitative method with purposive sampling technique. The Sample in this study was 80 patients with criteria, experience full awareness (composmentis) and literacy. Data was taken using a food record, then analyzed with Nutrisurvey software. Data were analyzed using frequency distribution. The results showed that sodium intake (55%), potassium (87.5%), calcium (53.75%), and phosphorus (46.25%) in most respondents in the normal category. Vitamin D intake in most respondents (70%) is in the less category. Most respondents get enough vitamin and mineral intake except vitamin D.Health workers are expected to provide ongoing education on the importance of maintaining intake of vitamins and minerals especially vitamin D in patients with chronic kidney diseases. In addition, health workers are expected to collaborate well in meeting the vitamin and mineral needs of patients with kidney diseases.